ENERGY SAVING TECHNOLOGY OF SURFACE TREATMENT OF URBAN RUNOFF - and and (Municipal economy of cities. Series: «Economy science», 2013)
It is proposed treatment technology of surface runoff, reducing the area under treatment plants, to simplify the process of preparation of water for reuse or discharge standards to clean the pond.